ANALISIS IMPLEMENTASI PELATIHAN BERBASIS KOMPETENSI (PBK) SEBAGAI MODEL PENDIDIKAN NONFORMAL DI BBPVP SERANG STUDI KASUS PROGRAM WELDING SMAW - Putri Larasati, Anisa; M. Syadeli Hanafi; Ahmad Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
To address unemployment and skill mismatches in Indonesia, Non-Formal Education through Competency-Based Training (CBT) is used for upskilling. This study analyzes CBT implementation in the SMAW Welding Program at BBPVP Serang, including planning, implementation, evaluation, NFE principles, and mitigation strategies.Using a qualitative descriptive case study, data were collected from instructors, staff, and trainees via observation, interviews, and documents, then analyzed with Miles and Huberman’s model.Findings show CBT is structured and adaptive. Planning follows KKNI Level II/SKKNI. Implementation uses 30% theory and 70% practice. Evaluation includes weekly pre-tests and final LSP-BNSP certification. NFE principles appear in flexible, andragogical, competency-based learning, with 80% graduate employment in 2025. Challenges like varied skills and overcapacity were solved by clustering and resource optimization.